2019
DOI: 10.1021/acs.jafc.9b02662
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biological Agent Cytosinpeptidemycin Inhibited the Pathogenesis of Tobacco Mosaic Virus by Inducing Host Resistance and Stress Response

Abstract: Cytosinpeptidemycin (CytPM) is a microbial pesticide that displayed broad-spectrum antiviral activity against various plant viruses. However, the molecular mechanism underlying antiviral activity of CytPM is poorly understood. In this study, the results demonstrated that CytPM could effectively delay the systemic infection of tobacco mosaic virus (TMV) in Nicotiana benthamiana and significantly inhibit the viral accumulation in tobacco BY-2 protoplasts. Results of RNA-seq indicated that 210 and 120 differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…Induction of ZAT12 is indicated to be closely related with the oxidative stress response, and serves as an abiotic stress marker [43]. Our previous work has shown that the biological agent of cytosinpeptidemycin significantly induced up-regulation of ZAT12 [20]. In this work, gene expression of ZAT12 was significantly up-regulated under NNM treatment.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Induction of ZAT12 is indicated to be closely related with the oxidative stress response, and serves as an abiotic stress marker [43]. Our previous work has shown that the biological agent of cytosinpeptidemycin significantly induced up-regulation of ZAT12 [20]. In this work, gene expression of ZAT12 was significantly up-regulated under NNM treatment.…”
Section: Discussionmentioning
confidence: 66%
“…The extracted RNA of each treatment group was adjusted to 10 μg and subjected to northern blot analysis as described [19] using a DIG High Prime DNA Labeling and Detection Starter Kit II (Roche, Mannheim, Germany). The digoxigenin-labelled RNA probes for TMV positive- and negative-strand RNA have been previously described [20]. The RNA signals were detected with a chemical luminous imaging system, Tanon 5200 (Tanon, Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…8 Some natural antivirals are also being commercialized, such as ningnanmycin 9 and cytosinpeptidemycin. 10 However, the creation and use of antivirals are still extremely limited as a result of complex syntheses, the ready decomposition of active components, their relatively low efficiency, high toxicity in non-target organisms, considerable pesticide resistance, and pesticide interactions. 11 Consequently, the development of novel, efficient, and environmentally friendly new antivirals is a top priority.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Plant viruses rely on interaction with multiple viral hosts for self‐multiplication and systemic infection 37 . Plant antiviral medicines can directly act on nucleic acid or viral coat protein to inhibit viruses, or indirectly change the balance of virus‐host interaction by regulating host response 38 . Previous studies have shown that extracellular proteins produced by beneficial microorganisms have antiviral activity.…”
Section: Discussionmentioning
confidence: 99%